Implementation of laser simulator in robot path determination - Zenas, Chung Han Yuan (2016)
The most important aspect for autonomous mobile robot to achieve its tasks is path planning. The path planning of autonomous robot is used to search a collision free path that a robot must take in order to pass over each point in an environment. The path is a plan of geometric locus points in a given space and the robot has to pass through it. In this research, the laser simulator search graph is a novel path planning approach which is proposed by Mohhammed A.H.Ali and the working principle of this approach is that the laser simulator is model as principle of real laser range finder. The environment of the robot is assume to be captured by camera and the laser range finder is used to measure the distance between robot and border. By using the measurement of distances, point in front of robot can be generated and this process repeat until the robot reach goal position. The developed laser simulator is then implemented by testing its performance in few different environments. In addition, one of the classical path planning approach which is A* algorithm will be used to compare the result generated by laser simulator. From this research, the laser simulator has advantages in computational time and low collision possibility compare with A* algorithm while the path cost of laser simulator is always greater than path cost of A* algorithm.